Exploiting sweetpotato as an animal feed in East Africa - International Potato Center (2014)
Sweetpotato offers great potential as an animal feed in sub-Saharan Africa (SSA). Research to identify appropriate dual-purpose varieties for Kenya & Rwanda, sweetpotato-based silage recipes and an improved silage tube was conducted by four students earning their Master’s degrees and scientists at CIP, ILRI, and the University of Nairobi.